2015
DOI: 10.3390/f6093256
|View full text |Cite
|
Sign up to set email alerts
|

Tree- and Stand-Level Thinning Effects on Growth of European Beech (Fagus sylvatica L.) on a Northeast- and a Southwest-Facing Slope in Southwest Germany

Abstract: Anticipated changes in climate and research findings on the drought sensitivity of beech have triggered controversial discussions about the future of European beech. We investigated the growth response of beech on the tree-and stand-level in mature stands to three different thinning intensities (no thinning, strong thinning, very strong thinning) on a northeast-and southwest-facing slope in Southwest Germany. Linear mixed-effects models were formulated to describe effects on growth parameters on the tree-and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 42 publications
5
16
0
Order By: Relevance
“…It is well known that different silvicultural treatments such as thinning increase radial growth. This has been shown also for European beech (Boncina et al 2007;Ottorini 1993, 1999;van der Maaten 2012;Diaconu et al 2015). In this context our results reveal that thinning might not only give higher radial growth rates but also higher wood density.…”
Section: Tree-ring Width Effectsupporting
confidence: 83%
“…It is well known that different silvicultural treatments such as thinning increase radial growth. This has been shown also for European beech (Boncina et al 2007;Ottorini 1993, 1999;van der Maaten 2012;Diaconu et al 2015). In this context our results reveal that thinning might not only give higher radial growth rates but also higher wood density.…”
Section: Tree-ring Width Effectsupporting
confidence: 83%
“…Yet, it is unlikely that the decrease of beech growth rate is related to thinning practices. Indeed, higher thinning intensity is rather known to increase the growth rate and the resilience to climate of mature beech trees [60][61][62]. The widespread use of harvesting machines in Belgium is more likely responsible for the alteration of the soil ecology, with adverse consequences on tree growth [9].…”
Section: Discussionmentioning
confidence: 99%
“…The results of many authors (Hein et al 2007;Boncina et al 2007;Štefančík 2015) confirmed that crown level thinning with positive selection are the most appropriate methods especially for growing of selective quality stands. The method of candidates (Schädelin 1934;Leibundgut 1966;Réh 2004), promising trees (Štefančík 1984) or target trees (Boncina et al 2007;Diaconu et al 2015;Štefančík 2015) is preferred. Advantages of the target trees method were also confirmed by Hein et al (2007), who based on a 35-year research found a higher stem quality and/or net value production on plots with thinnings and selected target trees in comparison with plots where interventions according to Assmann´s optimal basal area were performed.…”
Section: Commercial Quality Of the Standmentioning
confidence: 99%
“…Among these, different variants of low thinning (Foerster 1993;*Corresponding author. Igor Štefančík, e-mail: stefancik@nlcsk.org, phone: +421 45 5314 234 Utschig & Küsters 2003) and also crown thinning (Assmann 1968;Šebík & Polák, 1990;Hoffmann 1994;Štefančík et al 1996;Pretzsch 2005), both on the single tree or stand level (Diaconu et al 2015), were observed and compared mutually.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation